Pengaruh Suhu Terhadap Kadar Air pada Inti Sawit di Kernel Silo Pada Stasiun Kernel dengan Metode Rancangan Acak Kelompok - Rifka Annaria Sibuea; Dilla Nurfadiah; M.E. Ernawati Siregar; Irvina Abelia Harahap; Sudianto Manullang; Putri Maulidina Fadilah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
In the kernel processing process, it is important to understand the effect of temperature on the water content of the palm kernel in the kernel silo, especially at the kernel station. This study aims to analyze the effect of temperature on the water content of the palm kernel in the kernel silo at the kernel station. This study used the Randomized Block Design (RBD) method. Data were analyzed using linear regression and analysis of variance (ANOVA). By using the Randomized Block Design (RBD) method, the results of the treatment hypothesis were obtained that (285.241) > (2.44) which means that was rejected and could not be rejected, it can be concluded that the experiment of each temperature given had a significant effect on the resulting water content. In the results of the repetition hypothesis that (1.655) < (2.901) which means that could not be rejected and was rejected, it can be concluded that the experiment of each temperature given did not have a significant effect on the resulting water content.